Efeitos do inseticida organofosforado metil paration (Folisuper 600 BR) sobre biomarcadores do estresse oxidante no teleósteo de água doce matrinxã Brycon cephalus (GUNTER, 1869) - Monteiro, Diana Amaral (2006)
Methyl parathion (MP) is an organophosphorus insecticide worldwide used in agriculture and aquaculture due to its high activity against a broad spectrum of insect pests. It is employed as pesticide in agriculture and in food storage shelters, as well as in fish culture tanks to kill aquatic larval stages of insects. The effect of exposure to 2 ppm of a commercial formulation of MP (Folisuper 600 BR, methyl paration 600 g.L-1) on catalase (CAT), glutathione peroxidase (GPx), superoxide dismutase (SOD), glutathione S-transferase (GST), reduced glutathione (GSH) and lipid peroxidation (LPO) of the liver, white muscle, gills, erythrocytes and plasma of the freshwater fish matrinxã, Brycon cephalus, was evaluated after 96 h of treatment. MP exposure resulted in a significant induction of SOD and CAT activity in all tissues, except in plasma, when compared with controls. However, the GPx activity decreased significantly in the white muscle and gills, whereas no alterations were observed in hepatic, plasma and erythrocyte GPx activity. MP also induced a significant increase in GST activity in all tissues and a concurrent decrease in blood and tissue GSH levels. In addition, LPO values in the white muscle, gills and plasma increased significantly after MP exposure whereas hepatic and erythrocyte LPO levels did not show any significant alteration. The current data suggest that MP has oxidative-stress-inducing potential in B. cephalus, and that the gills and white muscle are the most sensitive organs with poor antioxidant potentials. The parameters studied in this investigation can also be used as biomarkers of exposure to MP. The antioxidant effect of selenium (Se) in reducing the MP-induced oxidative stress in this experimental model was evaluated in fish fed during 60 days, before exposure to 2 ppm of MP, with diets containing 1.5 mg Se.Kg-1 ration (group MP 1,5Se) or Se-free ration (group MP 0Se). Group MP 0Se exhibited, in all tissues, the same response presented by fish of the first experimental protocol, fed with commercial ration (group MP 0,22Se). Selenium supplementation reversed this trend. Significant increases in LPO levels and concurrent decreases in GPx activity in gills and white muscle were not observed in group MP 1,5Se. Similarly, decreases in GSH levels were not observed in any tissue of this experimental group. In addition, erythrocyte and plasma GPx activity also increased significantly in group MP 1,5Se, with a concomitant reduction and/or maintenance of LPO levels. These results suggest that dietary Se supplementation may protect cells against MP-induced oxidative stress, preventing increases in LPO levels and decreases in GSH content and GPx activity in B. cephalus tissues. According to these data Se supplementation is important to counteract the oxidative damage induced by MP in B. cephalus.